Solution processable high-performance infrared organic photodetector by iodine doping - Tian, Pin; Tang, Libin; Xiang, Jinzhong; Sun, Zhenhua; Ji, Rongbin; Lai, Sin Ki; Ping Lau, Shu; Kong, Jincheng; Zhao, Jun; Yang, Chunzhang; Li, Yanhui (RSC advances, 2016)
Solution processable high-performance, large-area, low-cost infrared organic photodetectors (OPDs) have been receiving more and more attention for their important applications both in scientific and technological fields. The search for a simple method to upgrade device performance for OPDs becomes increasingly important. Here, the performance of an OPD in the near-infrared (NIR) region is tremendously improved by doping iodine into the device's active layer (P3HT:PCBM:I 2 ), 2.7 wt% iodine doping may increase the absorption by 31.3% for the active film and result in a ∼11 000-fold increase in responsivity for the detector. A high detectivity ( D *) of ∼1.6 × 10 12 cm Hz 1/2 W −1 , a good specific responsivity ( R ) of ∼80 A W −1 and a large EQE (external quantum efficiency) of 120% are achieved under illumination ( λ = 850 nm) at room temperature. Systematic characterizations reveal that iodine-doping can introduce acceptor states in the energy band gap for the polymer layer, and thus increase the harvesting to long wavelength photons. A small dose of iodine doping can significantly induce improvement in device performance. This work demonstrates a simple but feasible method to enhance an NIR optoelectronics device. A high-performance IR OPV detector has been fabricated, 2.7 wt% iodine doping may increase the absorption by 31.3% for the active film thus result in the ∼11 000-fold increase in responsivity for the detector.